Community participation in regional tourism development: a case study in North Halmahera Regency - Indonesia - Yerik Afrianto Singgalen; Gatot Sasongko; Pamerdi Giri Wiloso (Insights into Regional Development)
This study aims to describe the community participation in regional tourism development from the perspective of Arnstein’s theory through ladder of participation in Pitu Beach as the top Tourist Destination of North Halmahera Regency, Indonesia. The primary data used in this study were obtained from the representatives of local government (district-subdistrict-village), youth organization, local entrepreneur community and stakeholders who involved in regional tourism development of North Halmahera. While the secondary data were obtained from the Public Works Office of North Halmahera Regency. The results show that community participation in regional tourism development showed the existence of the control society in tourism planning, implementing and evaluating the development program. Thus it could be proofed that community-based tourism approach had been successfully implemented in the context of North Halmahera, Indonesia.